Aluminum‐Ion Batteries: A Portable and Efficient Solar‐Rechargeable Battery with Ultrafast Photo‐Charge/Discharge Rate (Adv. Energy Mater. 28/2019). Issue 28 (26th July 2019) - Hu, Yuxiang; Bai, Yang; Luo, Bin; Wang, Songcan; Hu, Han; Chen, Peng; Lyu, Miaoqiang; Shapter, Joe; Rowan, Alan; Wang, Lianzhou
Abstract : In article number1900872, Lianzhou Wang and co‐workers report a portable and efficient solar‐rechargeable battery by integrating a perovskite solar module and an aluminum‐ion battery on the bifunctional aluminum electrode, which exhibits a fast photo‐charge/discharge rate and delivers a record overall photoelectric conversion and storage efficiency of 12.04%.